A study of igneous rocks related to Zn–Pb mineralization in the Shinyemi and Gagok deposits of the Taebaeksan Basin, South Korea. Issue 3 (21st January 2020) - Seo, Jieun; Choi, Seon‐Gyu; Koo, Minho; Oh, Chang Whan; Ryu, In–Chang; Lee, Gilljae
Abstract: The Shinyemi and Gagok deposits, located in the Taebaeksan Basin, South Korea, display Zn–Pb mineralization along a contact between Cretaceous granitoids and Cambrian–Ordovician carbonates of the Joseon Supergroup. The Shinyemi mine is one of the largest polymetallic skarn‐type magnetite deposits in South Korea and comprises Fe and Fe–Mo–Zn skarns, and Zn–Cu–Pb replacement deposits. Both deposits yield similar Cretaceous mineralization ages, and granitoids associated with the two deposits displaying similar mineral textures and compositions, are highly evolved, and were emplaced at a shallow depth. They are classified as calc‐alkaline, I‐type granites (magnetite series) and were formed in a volcanic arc. Compositional variation is less in the Shinyemi granites and aplites (e.g., SiO2 = 74.4–76.6 wt% and 74.4–75.1 wt%, respectively) than in the Gagok granites and aplites (e.g., SiO2 = 65.6–68.0 wt% and 74.9–76.5 wt%, respectively). Furthermore, SiO2 vs K/Rb and SiO2 vs Rb/Sr diagrams indicate that the Shinyemi granitoids are more evolved than the Gagok granitoids. Shinyemi granitoids had been already differentiated highly in deep depth and then intruded into shallow depth, so both granite and aplite show the highly evolved similar chemical compositions. Whereas, less differentiated Gagok granitoids were separated into two phases in the last stage at shallow depth, so granite and aplite show different compositions. The amounts of granites and aplite are similar in the Shinyemi deposit, whereas the aplite appears in an amount less than the granite in the Gagok deposit. For this reason, the Shinyemi granitoids caused not only Fe enrichment during formation of the dolomite‐hosted magnesian skarn but also was associated with Mo mineralization in the Shinyemi deposit. Zn mineralization of the Gagok deposit was mainly caused by granite rather than aplite. Our data suggest that the variation in mineralization displayed by the two deposits resulted from differences in the compositions of their associated igneous intrusions. Abstract : The geochemistry of Zn–Pb skarn deposit‐related igneous rocks was determined. Igneous rocks associated with the Shinyemi and Gagok skarn deposits in South Korea were compared. The associated granitoids display subvolcanic characteristics and mineral assemblages.